Neglected Pathological Fracture on the Proximal Femur Due to Simple Bone CYST: Successful Reconstruction Using Bone Graft and Osteosynthesis - Onarisa Ayu; Javier Arrazi (Eduvest - Journal of Universal Studies, 2026)
Simple Bone Cyst is a benign osteolytic lesion commonly found in children and adolescents, predominantly affecting the metaphyseal region of long bones such as the proximal humerus and femur. Although SBC is generally asymptomatic, it poses a significant clinical concern for its association with pathological fractures, particularly in weight-bearing bones. Pathological fractures of the proximal femur caused by SBC are relatively rare but may lead to functional impairment, delayed healing, and long-term disability if not managed appropriately. The absence of standardized treatment guidelines for neglected pathological fractures associated with SBC further complicates clinical decision-making. This study reports a case of an 11-year-old female patient presenting with a neglected pathological fracture of the proximal femur secondary to a simple bone cyst. Clinical evaluation and radiographic examination revealed a lytic lesion with cortical thinning accompanied by a fracture in the proximal femoral region. Surgical management was performed through biopsy and curettage of the cystic lesion, followed by open reduction and internal fixation using a locking plate and screws, combined with autologous bone graft harvested from the iliac crest. Postoperative follow-up at five months demonstrated satisfactory radiological and functional outcomes, including callus formation, stable fixation, and restoration of full range of motion without pain. This case highlights that surgical curettage combined with bone grafting and osteosynthesis is an effective treatment strategy for managing neglected pathological fractures of the proximal femur due to SBC. Early surgical intervention plays a crucial role in preventing recurrence, ensuring structural stability, and restoring functional outcomes in pediatric patients.